EFL Lecturers’ and Students' Perception towards Online Learning in Riau context: Using Technology Acceptance Model (TAM) as the Organizing Framework - Kurnia Budiyanti; Riza Amelia; Harum Natasha (Indonesian Journal of Integrated English Language Teaching, 2022)
Online learning in the pandemic has been conducted with less preparation by both the teachers and the students. Whether or not it has been effective, little is known. The research aims to conduct research on EFL lecturers’and students’ perception toward online learning from the perspective of technology acceptance model by Davis et al. (1989). The design of the reserch is descriptive quantitative. There were 14 EFL lecturers  and 121 EFL students recruited in the study. Data collection method was a questionnaire with a 5-Likert scale. Data analysis was descriptive statistics. The findings reveal that the lecturers’perceived usefulness and the perceived ease-of-use fall on high category (respectively, 72,95% and 71,1%) and the students’ lecturers’perceived usefulness and the perceived ease-of-use fall on high category (respectively, 79.10% and 72.50%). Out of all items, the lecturers mostly appreciated the flexibility of online learning in term of time and place (82.86%); and the students mostly appreciated the online learning’s opportunity to study English ((77,19%). Some suggestions are given to future researchers, namely (1) the next researcher can recruit more participants, (2) the next researcher can use different instruments to collect the data, like observation, interview and tests. Keywords: online learning, perceived usefulness, perceived ease-of-use, face-to-face.